Adapting the nitrogen replacement approach to dryland spring wheat in the Pacific Northwest. Issue 5 (3rd August 2017) - Long, Dan; McCallum, John; Reardon, Catherine; Engel, Richard
Abstract : The objective of this article is to summarize results of a study conducted in eastern Oregon to define the critical protein levels for dark northern spring and soft white spring wheats and their fertilizer nitrogen equivalent values. Earn 1 CEU in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/494 .